KEDUDUKAN HUKUM PERKAWINAN ADAT DI DALAM SISTEM HUKUM PERKAWINAN NASIONAL MENURUT UU NO. 1 TAHUN 1974 - Elsaninta Sembiring; Vanny Christina (Universitas Sebelas Maret, 2014)
Marriage is a natural human behavior. Humans were born, growing, mature , working , making a families and produce offspring. So marriage is a phase that will be experienced by people in general . Marriage occurs when two people of different sexes , that men and women are mutually bind themselves to live a life together in one household as husband and wife. Indonesia, which has a rich nation with diverse ethnic , cultural customs and led to the diversity of the Marriage Law is also based on the customs of each tribe are spread throughout Indonesia. Before having a national marriage law, Indonesia has had various legal rules pluralistic marriage . Birth of Law No. 1 of 1974 as a national marriage law unification bembawa certainly impact the Customary Marriage Law in Indonesia . Thus the authors will try to assess how the position of customary marriage law in the system according to the National Marriage Law Act Number 1 of 1974 .